The Relevance of Prophetic Leadership, Santri Organizational Culture and Basic Leadership Training to the Performance and Organizational Discipline of Al-Umm Aswaja Islamic Boarding School Students - Mohamad Abdi Baha; Indupurnahayu Indupurnahayu; Popy Novita Pasaribu (Universitas KH. Abdul Chalim Mojokerto, 2025)
The purpose of this study is to analyze the relevance of prophetic leadership, student organizational culture and basic leadership training as well as its influence on the performance and discipline of the management of student organizations at Al-Umm ASWAJA Islamic Boarding School. The research method used was a quantitative research method with 53 respondents through a questionnaire using a google form and analyzed using SPSS number processing software version 27. The results of the research based on SPSS analysis showed that Prophetic Leadership and Organizational Culture had no significant effect on performance. Prophetic Leadership and Basic Leadership Training have a non-significant effect on Discipline, while Basic Leadership Training has a significant effect on performance and organizational culture has a significant effect on discipline. Simultaneously, prophetic leadership, organizational culture and basic training have a significant influence on the performance and discipline of the management of the student organization at the Al-Umm ASWAJA Islamic Boarding School.